WRITING PATTERNS DEVELOPMENT WITH FOLKLORE IN MODERN FANTASY LITERATURE - Hilma Mufidah; Yosi Wulandari (IKIP Siliwangi, 2022)
This research was conducted on the curiosity of researchers related to the difficulty of finding studies and discussions of fantasy literature subject. That's why researchers tried to start research to prove fantasy literature could be created from developing local myth, especially, studies related to it are rarely found. The method chosen here is a qualitative descriptive comparative literary approach using intertextual theory by comparing webtoon 7 Wonders that developed its setting on the basis of Nawang Wulan figure from folklor